Produção de biomassa e composição química de adubos verdes cultivados no Vale do Ribeira - Lima, Juliana Domingues [UNESP]; Sakai, Ronaldo Kazuo; Aldrighi, Michel (Universidade Federal de Uberlândia (UFU), 2012)
The contribution of green manure to soil improvement and crop production depends primarily on biomass production and its chemical composition, which vary depending on the species, region and growing season. The aim of this research was to evaluate the chemical composition of biomass produced by green manures in Vale do Ribeira, São Paulo, Brazil. In order to develop this research, was carried an experiment in Pariquera-Acu, in 2006/2007, in completely randomized blocks design with four treatments (three green manure and spontaneous vegetation) and five replications. At 30, 60, 90 and 120 after sowing samples were collected in 1m(2) of the shoots and determined fresh and dry, and chemical composition biomass. Sunhemp, pigeon pea and mucuna produced, in decreasing order, the largest quantities of biomass and were more efficient than the spontaneous vegetation. The biomass produced by green manure had higher quality than that produced by spontaneous vegetation. Sunhemp and pigeon pea have a higher proportion of dry matter in stems which have low N, high C/N and L/N ratio, variables indicating slow decomposition of residues. The analysis of dry matter partitioned to better indication of the chemical composition of the residues and the prevision of the availability of nutrients in the soil.

A contribuição da adubação verde com leguminosas para melhoria do solo e produção agrícola depende em primeiro lugar da produção de biomassa e da sua composição química, que variam em função da espécie, região e estação de cultivo. Objetivo do presente trabalho foi avaliar a composição química da biomassa produzida por adubos verdes no Vale do Ribeira, São Paulo, Brasil. Para tal, foi conduzido um experimento em Pariquera-Açu-SP, no ano agrícola 2006/2007, em blocos casualizados, com quatro tratamentos (três adubos verdes e vegetação espontânea) e cinco repetições. Aos 30, 60, 90 e 120 dias após a semeadura, foram coletadas amostras em 1 m² da parte aérea das plantas e determinada a matéria fresca e seca, bem como a composição da biomassa. Crotalária, guandu e mucuna produziram, em ordem decrescente, as maiores quantidades de biomassa e foram mais eficientes do que a vegetação espontânea. A biomassa produzida pelos adubos verdes apresentou qualidade superior à produzida pela vegetação espontânea. Crotalária e guandu apresentam maior proporção de matéria seca acumulada no caule que possui baixo teor de N, alta relação C/N e L/N, variáveis que tornam a decomposição dos resíduos mais lenta. A análise particionada da matéria seca permite indicação mais precisa da composição química dos resíduos e a previsão da disponibilidade dos nutrientes no solo.
Biomass production e chemical composition of green manure cultivated in Vale do Ribeira
Keywords: Green fertilization; Crotalaria juncea; Mucuna deeringiana; Cajanus cajan; Residue quality; Nitrogen